Running 30 meters for boys and girls in first and second grades of elementary school - Y. Touvan Juni Samudro; Isti Dwi Puspita Wati; Maharani Fatima Gandasari; Ghana Firsta Yosika; Putra Sastaman B; Davi Sofyan (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The background of this research is the importance of the running ability of elementary school students. This study aims to determine differences in the ability to run 30 meters of elementary school students. The research was conducted by survey with a sample of elementary school students at Public Elementary School 27 Sungai Kakap Pontinak grades 1 and 2. The total sample size was 33 students, 16 boys, and 17 girls, with an age range of 6-8 years. The test is done by running 30 meters measured in seconds—data analysis using descriptive statistics and different tests. The study results showed a difference between the age groups between boys and girls for up to 1 second in covering a distance of 30 meters. It was concluded that running between boys and girls is better for boys. Based on the results of this study, it is hoped that the physical education program will provide more equal opportunities for both students to participate so that there are no gaps. As well as learning programs arranged in a pleasant atmosphere